Circulating miR‐19a‐3p and miR‐19b‐3p characterize the human aging process and their isomiRs associate with healthy status at extreme ages. Issue 7 (23rd June 2021) - Morsiani, Cristina; Terlecki‐Zaniewicz, Lucia; Skalicky, Susanna; Bacalini, Maria Giulia; Collura, Salvatore; Conte, Maria; Sevini, Federica; Garagnani, Paolo; Salvioli, Stefano; Hackl, Matthias; Grillari, Johannes; Franceschi, Claudio; et al.
Abstract: Blood circulating microRNAs (c‐miRs) are potential biomarkers to trace aging and longevity trajectories to identify molecular targets for anti‐aging therapies. Based on a cross‐sectional study, a discovery phase was performed on 12 donors divided into four groups: young, old, healthy, and unhealthy centenarians. The identification of healthy and unhealthy phenotype was based on cognitive performance and capabilities to perform daily activities. Small RNA sequencing identified 79 differentially expressed c‐miRs when comparing young, old, healthy centenarians, and unhealthy centenarians. Two miRs, that is, miR‐19a‐3p and miR‐19b‐3p, were found increased at old age but decreased at extreme age, as confirmed by RT‐qPCR in 49 donors of validation phase. The significant decrease of those miR levels in healthy compared to unhealthy centenarians appears to be due to the presence of isomiRs, not detectable with RT‐qPCR, but only with a high‐resolution technique such as deep sequencing. Bioinformatically, three main common targets of miR‐19a/b‐3p were identified, that is, SMAD4, PTEN, and BCL2L11, converging into the FoxO signaling pathway, known to have a significant role in aging mechanisms. For the first time, this study shows the age‐related increase of plasma miR‐19a/b‐3p in old subjects but a decrease in centenarians. This decrease is more pronounced in healthy centenarians and was confirmed by the modified pattern of isomiRs comparing healthy and unhealthy centenarians. Thus, our study paves the way for functional studies using c‐miRs and isomiRs as additional parameter to track the onset of aging and age‐related diseases using new potential biomarkers. Abstract : Small RNA deep sequencing on plasma‐derived RNA from 12 donors (young and old subjects, healthy, and unhealthy centenarians) was performed: 79 differentially expressed c‐miRs were identified. MiR‐19a/b‐3p increased at old age but decreased at extreme age, as confirmed by RT‐qPCR in 49 subjects. The decrease was more relevant in healthy centenarians, also confirmed by the modified pattern of isomiRs. Three common targets of miR‐19a/b‐3p were identified converging into the FoxO signaling pathway.